Modeling of Power Generation using Municipal Solid Waste in India - Shrikant B Karajgi; Udaykumar R Yaragatti; Gopal D Kamalapur (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Generation of Electrical Energy from Municipal Solid Waste (MSW) is acomplex process since the waste has to undergo various unit processes before it is put in to the process of energy production. The modeling of power generation from MSW, therefore has to include all these unit processes, waste flow paths etc. The modeling must also be capable of providing information on important issues like economical, environmental among many others. With the launching of new energy policy by Govt. of India, on liberalization of energy production, Independent power producers (IPP) are exploring Municipal Solid Waste (MSW) as a main source of energy in addition to other renewable sources like fuel cells, solar, wind etc. for production of energy at affordable rates. In this paper, a mathematical model of the power generation using MSW is examined, keeping in view, the composition of waste in India. Linear equations have been developed for the various waste flow paths and the mass balance equations are then solved for the main objective function of minimum cost.DOI:http://dx.doi.org/10.11591/ijece.v2i2.270